Vilka stereotypier finns hos brunbjörn (Ursus arctos), lodjur (Lynx lynx) och varg (Canis lupus) i djurpark och vilka berikningar finns? : förslag och rekommendationer om berikningar utifrån djurens beteendeekologi - Dahlman, Nicole (SLU/Dept. of Animal Environment and Health (until 231231), 2010)
The purpose of this work was that with the help of a literature review have a single document with information on how the various species: brown bear (Ursus arctos), lynx (Lynx lynx) and the wolf (Canis lupus) living in the wild. The aim was also to show which stereotypic behaviours these different species have in zoos and the enrichments that is already being used and to make suggestions and recommendations on enrichment based on animal behaviour ecology. In zoos, some species thrive well while others have propositions to propagating problems, poor health and stereotypic behaviors. The brown bear, lynx and wolf, live both in the wild and in zoos in Sweden. As these animals have different ways of living in the wild, it is important to accommodate to each species, the way they are kept in zoos in accordance with their behavioural ecology. Brown bears are omnivorous and solitary living species with large energy needs so that they spend most of their day to actively feeding but also rest. Brown bears prefer a habitat that is a mixture of open and covered land. Brown bears have a promiscuous mating system and the mating period is between May and early July. Bears show a lot of different stereotypic behaviours in zoos. Lynx is a solitary living predator. These cats are in need of large contiguous forest habitats and want to have different habitat for hunting, eating the prey and rest. The premier food is roe deer (Capreolus capreolus). Lynx hunt by persecute and stalking the prey to start the attack from a short distance. Lynx has dispersed promiscuous system where mating period is between January and April. Lynx show some different stereotypic behaviours in zoos but the most common is pacing. Wolves are social animals that live mostly in packs with a monogamous alpha pair. They have a linear dominance hierarchy. Wolves prefer a mixed habitat. The principal food is moose (Alces alces) that wolves typically only can catch where they hunt in packs. The mating period of wolves is between January and the beginning of ...